2017
DOI: 10.5539/gjhs.v9n12p131
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Attitudes towards Smoking and Anti-Smoking Measures among Korean Male Smokers in Australia

Abstract: The study aims to explore how Korean male smokers living in Australia talk and feel about smoking and how they have understood and experienced tobacco control policies in Australia-including price increase, display ban, plain packaging, and graphic warning labels. A qualitative study was conducted based on in-depth face-to-face interviews with 8 Korean male smokers aged 23-40 years living in Canberra. Participants discussed social and cultural conditions in Korea under which smoking is practiced and maintained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Stress and loneliness leading to tobacco use has been reported in many places. 20 Smoking and use of SLT as a means of socialization and relaxation were consistently discussed as the main reason for continued tobacco use. 15,17 Other studies reported common reasons for smoking for all participants were to relieve boredom (58.3%) followed by the need to feel relaxed (46.9%), to relieve anger and frustration (42.2%), to relieve pressure of working hard (27.2%), to concentrate at work (24.2%), and to mix in social situations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress and loneliness leading to tobacco use has been reported in many places. 20 Smoking and use of SLT as a means of socialization and relaxation were consistently discussed as the main reason for continued tobacco use. 15,17 Other studies reported common reasons for smoking for all participants were to relieve boredom (58.3%) followed by the need to feel relaxed (46.9%), to relieve anger and frustration (42.2%), to relieve pressure of working hard (27.2%), to concentrate at work (24.2%), and to mix in social situations.…”
Section: Discussionmentioning
confidence: 99%
“…13 Stress and loneliness for initiating this practice were found in studies conducted by other researchers. [21][22][23] Studies have also quoted occupational stress 20,24 specifically responsible for high smoking prevalence.…”
Section: Discussionmentioning
confidence: 99%